Stress proteins co-expressed in suberized and lignified cells and in apical meristems (Plant Science, 1998)
We report the cloning of a small heat shock protein, Qs –HSP17, and an osmotin like protein, Qs –OLP, from cork oak phellem tissue (cork cells). Both genes are expressed in suberizing cells and in other cells subject to endogenous stress associated with free radicals. We provide evidence that smHSPs and OLPs accumulate in overwintering buds and speculate that their role is similar to that in seed dormancy. We also show that both stress proteins are mainly located in the region of the quiescent center in root apex and in central meristem in the shoot apex. We emphasize that smHSPs and OLPs are expressed in cells growing under endogenous stress or facing long life-span. We discuss a possible role of these stress proteins against oxidative stress